2013
DOI: 10.2174/1874300501307010006
|View full text |Cite
|
Sign up to set email alerts
|

Survival after Complete Mesocolic Excision (CME) for Right Sided Coloncancer Compared to Standard Surgery

Abstract: Abstract:Purpose: Complete mesocolic excision for right sided colon cancer is a complex operation that might offer a survival benefit. However, studies comparing CME to standard surgery have not been published so far.Methods: One-hundred-seven patients were operated at the discretion of the surgeon either according to principles of complete mesocolic excision (CME-group, n=69) or received a standard right hemicolectomy (non-CME group, n=38). The type of surgery was prospectively recorded.Results: Patients in t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
7
0
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 13 publications
0
7
0
1
Order By: Relevance
“…TNM stages ranged between I and III. Three studies included only laparoscopic surgery [ 15 , 19 , 20 ], and one study only open surgery [ 30 ]. Newcastle–Ottawa Scale scores ranged between 6/9 and 8/9.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…TNM stages ranged between I and III. Three studies included only laparoscopic surgery [ 15 , 19 , 20 ], and one study only open surgery [ 30 ]. Newcastle–Ottawa Scale scores ranged between 6/9 and 8/9.…”
Section: Resultsmentioning
confidence: 99%
“…All studies comparing CME versus non-CME reported a statistically significant increase in harvested lymph nodes in favour of the CME technique, with mean values ranging between 22.6 and 57.9 lymph nodes for the CME group and between 14.0 and 50.4 lymph nodes for the non-CME group [ 15 , 17 , 19 24 , 30 ]. Meta-analysis found that CME increased the number of harvested lymph nodes by 9 lymph nodes when compared to non-CME (9 studies, 3955 patients, MD 9.03, 95% CI 5.36–12.71, p < 0.00001, I 2 95%) (Fig.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In recent years, exact dissection along the embryological layer with radical lymphadenectomy up to the mesenteric vessels (complete mesocolic excision (CME)) has become a focus of attention (3). Analogous to total mesorectal excision (TME) for rectal cancer, this surgical procedure has significantly improved the oncological outcome compared with conventional lymphadenectomy (3)(4)(5). However, CME is a technically demanding procedure.…”
Section: Introductionmentioning
confidence: 99%
“…Hohenberger stellte dieses Konzept der CME 2009 vor und konnte damit eine tumorspezifische 5-Jahres-Überlebensrate von 89 % in den Stadien UICC I-III erreichen. In einem prospektiven, nichtrandomisierten Vergleich konnte unsere Arbeitsgruppe diese Daten bestätigen [6]. Unterstützt wurde das Konzept zudem durch Publikationen, die eine Korrelation zwischen intakten Grenzlamellen und der Prognose zeigen konnten.…”
unclassified